American Radium Society (ARS) Appropriate Use Criteria (AUC) for Locoregional Gastric Adenocarcinoma: Systematic Review and Guidelines. (10th September 2022) - Kumar, Rachit; Tchelebi, Leila; Anker, Christopher J.; Sharma, Navesh; Bianchi, Nancy A.; Dragovic, Jadranka; Goodman, Karyn A.; Herman, Joseph M.; Jiang, Yixing; Jones, William E.; Kennedy, Timothy J.; Lee, Percy; et al.
Abstract : Objective: The objective of this study was to systematically evaluate the data regarding the use of neoadjuvant, perioperative, surgical, and adjuvant treatment options in localized gastric cancer patients and to develop Appropriate Use Criteria recommended by a panel of experts convened by the American Radium Society. Methods: Preferred reporting items for systematic reviews and meta-analyses methodology was used to develop an extensive analysis of peer-reviewed phase 2/2R/3 trials, as well as meta-analyses found within the Ovid Medline database between 2010 and 2020. The expert panel then rated the appropriateness of various treatments in 5 representative clinical scenarios through a well-established consensus methodology (modified Delphi). Results: For patients with medically operable locally advanced gastric cancer, the strongest recommendation was for perioperative chemotherapy based on high-quality data. Acceptable alternatives included surgery followed by either chemotherapy or concurrent chemoradiotherapy (CRT). For patients with upfront resection of stages I to III gastric cancer (no neoadjuvant therapy), the group strongly recommended adjuvant therapy with either chemotherapy alone or CRT, based on high-quality data. For patients with locally advanced disease who received preoperative chemotherapy without tumor regression, the group strongly recommended postoperative chemotherapy or postoperative CRT. Finally, for medically inoperable gastric cancer patients, there was moderate consensus recommending definitive concurrent CRT. Conclusions: The addition of chemotherapy and/or radiation, either in the neoadjuvant, adjuvant, or perioperative setting, results in improved survival rates for patients compared with surgery alone. For inoperable patients, definitive CRT is a reasonable treatment option, though largely palliative.